ANALISIS KESULITAN MEMBACA PERMULAAN PADA PESERTA DIDIK KELAS III - Indah Tri Monica; Wawan Syahiril Anwar, Fitri Anjaswuri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research describes the early reading difficulties experienced by elementary school students. The study employed a qualitative approach using a case study method. The research subject was one student who demonstrated significant challenges in early reading. Data were collected through observation, interviews with teachers, the student, and parents, and documentation. The findings indicated that the student's reading difficulties were caused by various factors, both internal (such as lack of concentration and learning motivation) and external (such as insufficient guidance from family and school environment). The interventions included individual tutoring and the use of learning media. This study recommends more adaptive instructional approaches and stronger support from the surrounding environment to help overcome early reading difficulties.